Perlindungan Hukum Preventif Terhadap Kejahatan Skimming dalam Layanan Anjungan Tunai Mandiri - Andina Resty Eliza Andina; Rasina Padeni Nasution (Verdict: Journal of Law Science, 2026)
The development of information technology in the banking sector has facilitated financial transactions through Automated Teller Machine (ATM) services. However, these advancements have also increased the risk of cybercrime, particularly skimming, which involves the unauthorized acquisition of customers’ ATM card data for fraudulent purposes. This crime causes financial losses to customers and raises legal issues concerning consumer protection in banking services. This study aims to analyze the legal framework governing skimming crimes in Indonesia and examine banks’ legal obligations in implementing preventive legal protection. The research employs an empirical juridical method with a descriptive-analytical approach using statutory analysis and interviews with banking institutions. The findings show that the legal regulation of skimming is governed by the Electronic Information and Transactions Law, the Consumer Protection Law, the Banking Law, as well as regulations issued by Bank Indonesia and the Financial Services Authority. Banks are required to implement the prudential banking principle by strengthening technological security systems, monitoring ATM operations, applying fraud detection mechanisms, and providing customer education on cybercrime risks. Despite these preventive measures, challenges remain due to the increasingly sophisticated methods used by cybercriminals and the limited public awareness of cybersecurity. Therefore, strengthening banking security, regulatory supervision, and public legal awareness is essential to prevent skimming.